Fortalecimiento de los procesos de gestión en la recuperación de cartera de las cooperativas de ahorro y crédito del segmento 1 de Cotopaxi - Recalde Tapia, Byron Rene (2023)
The present work entitled Strengthening of the management processes in the portfolio recovery of the savings and credit cooperatives of segment 1 of Cotopaxi, had the objective of strengthening the management processes in the portfolio recovery of the savings and credit cooperatives from segment 1 of Cotopaxi. For this purpose, the investigation was carried out in the El Sagrario Savings and Credit Cooperative. Starting from an analysis of the current processes of the company, a descriptive study was proposed, using primary sources, times were optimized, for which it was also considered as a field study, through the application of empirical observation methods in the study experience through procedural description. Together, the results of the main indicators of the segment 1 cooperative sector that measure delinquency, liquidity, solvency and profitability were analyzed as a guide for decision-making based on the design of the management model for portfolio recovery. Regarding secondary sources, different books, scientific articles, official documents were used, they have been carefully analyzed to determine the concepts that were used in this investigation. Among the most relevant results, the following stood out: the evolution of the non-performing portfolio index from 2019 to 2021 in microcredits from 5.3% to 5.5%; priority consumption from 2.78% to 3.45%; in real estate from 2.9% to 3.1%; the productive from 1% to 1.1%; in education from 1.8% to 4.3%. Finally, it was possible to conclude that the Cooperative maintained a high percentage of overdue portfolio, that there are liquidity problems in the productive activities of the members and that its collection process is static.